Beam-hardening in 70-kV Coronary CT angiography: Artifact reduction using an advanced post-processing algorithm. Issue 101 (April 2018) - Albrecht, Moritz H.; Bickford, Matthew W.; Schoepf, U. Joseph; Tesche, Christian; De Santis, Domenico; Eid, Marwen; Jacobs, Brian E.; Duguay, Taylor M.; Schmidt, Bernhard T.; Canstein, Christian; Varga-Szemes, Akos; Leithner, Doris; et al.
Abstract: Purpose: To investigate the effect of an iterative beam-hardening correction algorithm (iBHC) on artifact reduction and image quality in coronary CT angiography (cCTA) with low tube voltage. Material and methods: Thirty-six patients (17 male, mean age, 57.3 ± 14.5 years) were prospectively enrolled in this IRB-approved study and underwent 70-kV cCTA using a third-generation dual-source CT scanner. Images were reconstructed using a standard algorithm (Bv36) both with and without the iBHC technique. Several region-of-interest (ROI) measurements were performed in the inferior wall of the left ventricle (LV), an area prone to beam-hardening, as well as other myocardial regions. Coronary contrast-to-noise (CNR) and signal-to-noise ratios (SNR) were calculated. Two radiologists assessed subjective image quality. Results: The iBHC algorithm generally increased myocardial attenuation in all ROIs ( P <  0.566); however, the increase was significantly more distinct in beam-hardening prone areas such as the inferior LV (increase, +13.9 HU, +18.6%, P <  0.001), compared to the remaining myocardium (increase, +4.4 HU, +4.5%, P <  0.003). While no significant difference was found for image noise ( P <  0.092), greater CNR and SNR values for the left main coronary artery (increase, +20.7% and +17.3%, respectively) were found using the iBHC algorithm (both with P  < 0.001). Subjective image quality was comparable between both image series ( P  = 0.217). Conclusion: The iBHC post-processing algorithm leads to significantly reduced beam-hardening while providing improved objective and equivalent subjective image quality in 70-kV cCTA.